PROJECT-BASED LEARNING AS THE PRIORITY OF THE PROFESSIONAL TEACHER - Podavets, O.D.; Danilova, V.V. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
The given article is devoted to the problem of identifying inversion in modern English prose (on the basis of “Crome Yellow” by Aldous Huxley). The authors scrutinize various types of inversion and its functions based on traditional and alternative approaches. The authors present the set of examples illustrating inversion of both types: stylistic and grammatical.The conclusions demonstrate qualitative and quantitative results of the work done. The full text of the work has been reflected in the diploma project of the student.
Keywords: inversion; prose; stylistics; grammar; function